Giant thymolipoma in association with myasthenia gravis - Cekirdekci, Ahmet; Akpolat, Nusret; Ayan, Erhan; Duran, Mehmet (My University, 2003)
[Abstract Not Available]
Keywords: Myasthenia gravis; Thymolipoma